2004
DOI: 10.1093/toxsci/kfh027
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity and Interaction Effects of 14 Different Pyrethroids on Voltage-Gated Chloride Ion Channels

Abstract: We have proposed that since the type II pyrethroids deltamethrin and cypermethrin, but not the type I pyrethroid cismethrin act on chloride channels, this could contribute to the bimodal nature of pyrethroid poisoning syndromes. We now examine a wider range of pyrethroid structures on the activity of these calcium-independent voltage-gated maxi-chloride channels. Excised inside-out membrane patches from differentiated mouse neuroblastoma cells were used, and mean channel open probabilities calculated. For sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 13 publications
2
58
1
Order By: Relevance
“…Cypermethrin blocks sodium channels of nerve filaments by lengthening their depolarisation phase as well as affecting gamma-aminobutyric acid receptors and chloride and calcium channels in nerve filaments (Bradbury and Coats 1989b;Hayes 1994;Burr and Ray 2004). Cypermethrin contains chlorine atoms in a vinyl side chain of the compound.…”
Section: Original Papermentioning
confidence: 99%
“…Cypermethrin blocks sodium channels of nerve filaments by lengthening their depolarisation phase as well as affecting gamma-aminobutyric acid receptors and chloride and calcium channels in nerve filaments (Bradbury and Coats 1989b;Hayes 1994;Burr and Ray 2004). Cypermethrin contains chlorine atoms in a vinyl side chain of the compound.…”
Section: Original Papermentioning
confidence: 99%
“…Pyrethroids prolong the opening of the voltage-sensitive sodium channel (VSSC) and raise a prolonged sodium tail current in mammalian as well as invertebrate neurons (Vijverberg et al, 1982;Narahashi, 1985). Furthermore, it has been reported that pyrethroids act on not only VSSC but also other ion channels or neurotransmitter receptors, such as voltagegated chloride channels (Burr and Ray, 2004) and GABA A receptors (Crofton and Reiter, 1987). In contrast, we have already demonstrated that relatively high concentrations (more than 10 M) of pyrethroid insecticides decreased the expression of c-fos and BDNF genes induced by membrane depolarization in mouse cerebellar granule cells (Imamura et al, 2000).…”
mentioning
confidence: 99%
“…While excretion of various pyrethroids in the birds and mammals is about 6-12 hours, it is 48 hours in the trout. Like all pyrethroids "Bifenthrin" is highly toxic to fish, interfering with Na + channel gating in the nerve cell endings, but other ion channels such as Cl -and Ca + channels can be targeted as well [37]. This leads to continuous neurotransmission causing hyperexcitability, tremors, convulsions and finally death.…”
Section: Organophosphates (Op)mentioning
confidence: 99%